Study and Analysis of Education System in Nepal and Its Challenges Along with Its Solution - Sah, Prince; Sah, Rabi; Sahani, Suresh Kumar; Sahani, Kameshwar (Mikailalsys Journal of Advanced Engineering International, 2024)
This document represent the education system in Nepal and we also want to mention the challenges and its solution to improve the quality of education in Nepal. In this project work, we highlight the evolution and present status of Nepal The project begins with the concept of education, historical background and evolution of education in Nepal and it’s also include the structure of education system in Nepal. Furthermore, the project explores the challenges and its solution of education system in Nepal.